LOV OG RET I ANTROPOLOGISKE STUDIER AF MENNESKERETTIGHEDER - Wilson, Richard Ashby (Tidsskriftet Antropologi, 2008)
This article seeks to complement the now well-established anthropological emphasis on the discursive and social movements’ aspects of human rights by focusing on their legal character, and examining how law shapes the ability of local actors to pursue discursive and political strategies within a rights paradigm. The article begins by examining historical debates over the model of legal pluralism and argues that we might be better served by making a distinction between human rights law and human rights talk and then focusing upon four specifi c legal and social processes; the legalization of rights, rights and the verticalization of confl ict, the vernacularization of rights and the construction of truth and knowledge through the methods of legal investigation. The article concludes with a call for anthropologists to venture into the sites of production of international human rights law and norms and to gain access to international criminal tribunals and examine their internal legal procedures and their practices to establish knowledge. Researchers need to document and analyze how the verticalization of a national confl ict occurs at the UN, and how legal and political experts who author rights treaties respond to the hybridization and vernacularization of the terms they have sought to define.